EFFICIENCY OF INTRODUCTION OF ACTIVE SCREENING AND EXPRESS METHODS OF DETECTING OF TUBERCULOSIS IN THE REPUBLIC OF TAJIKISTAN - F.O. MIRZOEVA (Avicenna Tajik State Medical University, 2018)
Objective: To study the effectiveness of using active screening in identifying people with suspected tuberculosis, as well as express methods for diagnosing patients with tuberculosis in the Republic of Tajikistan. Methods: This study included persons who applied for medical institutions to primary health care (PHC) facilities for the period from 2011 to 2015 years in Dushanbe, Tursunzade, Khujand, Kanibadam and the regions of Gonchi, Mastchoh and Rudaki, which were screened for complaints and anamnestic data. All persons suspected of having tuberculosis underwent a complete clinical, x-ray examination and sputum research by two quick methods (microscopically and on the GeneXpert device), as well as sowing culture with subsequent determination of drug resistance on the Bactec MGIT apparatus. Results: Under our observations, there were 214,434 persons with suspicion of tuberculosis, from among which it was revealed 22,349 patients with different clinical forms of tuberculosis, which amounted to 10.4%. In the observed group of men there were 13887 (62.1%), women - 8462 (37.9%). Of the total number of patients, most (n=14100) included in the age group 19-44 years (63.1%) and 8249 people (36.9%) were from the age group of 45-69 years. Of the 22,349 tuberculosis patients, 65.5% suffered pulmonary tuberculosis with bacterial excretion, 25.1% - pulmonary tuberculosis without bacterial excretion and 9.4% - extrapulmonary tuberculosis. In 7.3% of cases, multiple drug resistance was detected, and in 92 patients (0.41%) - a combination of the active form of tuberculosis with HIV infection. Comparative study of the detection rate of new cases of tuberculosis over the same period in the study regions exceeded this indicator in other representative control regions twice. The beginning of the treatment after verification of the diagnosis was 3 days. Conclusion: The introduction of active screening in institutions of PHC facilities promotes a more effective integration of the phthisiatric services with the network of institutions of PHC facilities. In the implementation of active screening in 10.4% of cases, varifies different clinical forms of the disease.